2020
DOI: 10.1101/2020.04.09.20056374
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“Mental health status of the general population, healthcare professionals, and university students during 2019 coronavirus disease outbreak in Jordan: a cross-sectional study”

Abstract: Background:The emergence of COVID-19 global pandemic coupled with high transmission rate and mortality has created an unprecedented state of emergency worldwide. This global situation may have a negative impact on the psychological well-being of individuals which in turn impacts individuals' performance.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
139
4
17

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(179 citation statements)
references
References 35 publications
19
139
4
17
Order By: Relevance
“…According to the some studies during a pandemic; compliance rates were associated with some demographic characteristics: female and healthcare workers had higher overall compliance scores than male and other occupational groups (34,35). Compared with the general population, health care providers have higher health literacy as well as, due to duty calls, they are more likely to come in contact with COVID-19 carriers putting them at a greater risk of contracting the infection and spreading it to others (36). Therefore, it is to be expected that engagement in the preventive behaviors was significantly higher in the healthcare providers than other occupational groups.…”
Section: Discussionmentioning
confidence: 99%
“…According to the some studies during a pandemic; compliance rates were associated with some demographic characteristics: female and healthcare workers had higher overall compliance scores than male and other occupational groups (34,35). Compared with the general population, health care providers have higher health literacy as well as, due to duty calls, they are more likely to come in contact with COVID-19 carriers putting them at a greater risk of contracting the infection and spreading it to others (36). Therefore, it is to be expected that engagement in the preventive behaviors was significantly higher in the healthcare providers than other occupational groups.…”
Section: Discussionmentioning
confidence: 99%
“…The mental health impact of a disease outbreak is usually neglected during pandemic management although the consequences are costly [4]. Early evidence has shown that health workers directly involved in the diagnosis, treatment, and care of patients with COVID-19 are at risk of developing mental health symptoms [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Psychological wellbeing has an important impact on individuals' performance. The impact of COVID-19 on mental health is well documented in various countries among different populations including health professionals [4]. However, evidence regarding the impact of the COVID-19 pandemic on health professionals is not available in Nepal.…”
Section: Introductionmentioning
confidence: 99%
“…During pandemic management, the impact of outbreak on mental health is usually neglected though pandemic can trigger common mental disorders 4,5 . Evidence has shown that with the increase in the number of cases and deaths from COVID 19, health care workers have been experiencing psychological problems, with disability and functional impairment [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%